Manipulation of ferrofluid droplets on an open planar surface - Chua, Yong Chin. (2010)
In this project, the characteristics of ferrofluid droplets on open planar surface will be studied. By means of a permanent magnet, the author will try to manipulate the movement of ferrofluid droplets and also to investigate on the factors affecting the movements of the ferrofluid droplets.